2010
DOI: 10.1177/1941738110386185
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Versus Autograft Anterior Cruciate Ligament Reconstruction

Abstract: Background:Tearing an anterior cruciate ligament (ACL) graft is a devastating occurrence after ACL reconstruction (ACLR). Identifying and understanding the independent predictors of ACLR graft failure is important for surgical planning, patient counseling, and efforts to decrease the risk of graft failure.Hypothesis:Patient and surgical variables will predict graft failure after ACLR.Study Design:Prospective cohort study.Methods:A multicenter group initiated a cohort study in 2002 to identify predictors of ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 435 publications
(239 citation statements)
references
References 38 publications
11
220
0
8
Order By: Relevance
“…It has also been shown that the risk of graft failure decreases with increasing age. 16 Therefore, the studies in this systematic review did not evaluate allograft use in the highest risk population for graft failure, and this fact could bias the findings. Application of the findings of this study to a younger, more active population would not be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the risk of graft failure decreases with increasing age. 16 Therefore, the studies in this systematic review did not evaluate allograft use in the highest risk population for graft failure, and this fact could bias the findings. Application of the findings of this study to a younger, more active population would not be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,6,7,8,15,18,20,22,32,40,42,43 Our previous modeling longitudinally followed over 400 ACLR subjects at 2 and 6 years. 39 Despite identifying many significant risk factors for worse outcomes, we had insufficient sample size to determine if meniscal and articular cartilage pathology documented at the time of index ACLR has any effect on patient-reported outcomes following ACLR.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that subsequent ACL injuries occur with a higher frequency than previously thought; however, variability in the reported rate of second injuries remains. 12,26,29,33 Wright et al 33 prospectively reported that 1 in 17 (6%) patients sustained a second ACL injury within 2 years after ACLR. Of these, an equal occurrence of ipsilateral retears and contralateral tears was observed.…”
mentioning
confidence: 99%